Chitosan/polyvinyl alcohol nanofibrous membranes: towards green super-adsorbents for toxic gases. Issue 4 (April 2019) - Sargazi, Ghasem; Afzali, Daryoush; Mostafavi, Ali; Shadman, Alireza; Rezaee, Babak; Zarrintaj, Payam; Saeb, Mohammad Reza; Ramakrishna, Seeram; Mozafari, Masoud
Abstract: Removal of hazardous gases from the atmosphere has become a big challenge for scientists and engineers alike. Eco-friendly nature of biopolymers has given a new dimension to the debate within the environmental science area but attempts mainly failed to cleanse the air stream of toxic gases as a consequence of design imperfections. In this work, green electrospun nanofibrous membranes based on chitosan (Cs)/polyvinyl alcohol (PVA) composite with a very high carbon monoxide adsorption capacity (much higher than the values one may expect from activated carbon and zeolite adsorbents, and also higher than that of the metal-organic framework) are developed. 2 k−1 factorial design, response surface and desirability function analyses are merged to optimize the electrospinning parameters for functional-based carbon monoxide elimination. The best Cs/PVA adsorbent obtained through multi-objective optimization has a very high desirability value level of 0.953. Optimized electrospinning parameters are: Voltage = 17 kV, spinning distance = 13 cm, flow rate = 0.2 mL/h, and PVA concentration = 6 wt.%; and optimized properties are: maximum thermal stability = 329 °C, minimum fiber diameter = 9.8 nm, and maximum surface area = 2204 m 2 /g. This work opens a new era for taking the next steps towards the design and optimization of green super-adsorbents for gaseous contaminations.